Advances in the Development of Liquid Metal-Based Printed Electronic Inks - Wang, Lei; Liu, Jing (Frontiers in Materials, 2019)
As a newly emerging additive manufacturing technology, printed electronics based on the printing principle has received more and more attention. Compared to conventional electronics manufacturing, such technique has many advantages such as speediness, flexibility, personalized customization, and low cost. Currently, there are three kinds of typical conductive inks used in printed electronics—conductive carbon ink, conductive polymer, and metal conductive ink. However, the electrical conductivities of the conductive carbon ink and the conductive polymer are typically lower than 105 S/m, which impedes their application in high-sensitivity circuit fabrication. As to the metal conductive ink, post-treatments via long time curing process are often needed, which reduce the printing speed and improve the manufacturing costs. As an alternative, liquid metal is emerging as a new class of conductive ink and is thus becoming an important research focus. Such material has unique merits such as high electrical conductivity, simple preparation process, requesting no post-processing after printing, and so on. To further push forward the research on liquid metal-based printed electronics, this article strives to present an overview on the related research advancement in recent years. Properties of liquid metal such as oxidation, wettability, and conductivity are discussed. Liquid metal techniques including tapping mode electronic printing, atomized spray printing, microcontact printing, laser sintering method of liquid metal nanoparticles, transfer printing, masked deposition, liquid metal corrosion sculpture method, colorful liquid metal circuit fabrication method, and hybrid rolling and transfer printing method are systematically expounded. Prospective direction worth pursuing is outlined.